2020
DOI: 10.1002/ppul.24708
|View full text |Cite
|
Sign up to set email alerts
|

Deviations of body functions and structure, activity limitations, and participation restrictions of the International Classification of Functioning, Disability, and Health model in children with cystic fibrosis and non–cystic fibrosis bronchiectasis

Abstract: Background To the best of our knowledge, there is no study in the literature investigating the extrapulmonary outcomes of children with non–cystic fibrosis (CF) bronchiectasis and CF under the framework of the International Classification of Functioning, Disability, and Health (ICF) model. The purpose of the present study is to evaluate the children with CF and non‐CF bronchiectasis using the ICF model. Materials and Methods Children with CF, non‐CF bronchiectasis, and healthy counterparts were evaluated (20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…In fact, we did not observe significant correlations between lung function and TGlittre time. Our findings are in agreement with the study by Almeida et al (2021) worthy that, unlike TGlittre, 6MWD was correlated with spirometry in previous studies evaluating CF people (Ozipek et al, 2020;Ribeiro Moço et al, 2015;Troosters et al, 2009). Thus, it is possible that the 6MWD performance may depend more on the ventilatory reserve than the TGlittre time, especially because the 6MWT takes longer to complete (Marinho et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, we did not observe significant correlations between lung function and TGlittre time. Our findings are in agreement with the study by Almeida et al (2021) worthy that, unlike TGlittre, 6MWD was correlated with spirometry in previous studies evaluating CF people (Ozipek et al, 2020;Ribeiro Moço et al, 2015;Troosters et al, 2009). Thus, it is possible that the 6MWD performance may depend more on the ventilatory reserve than the TGlittre time, especially because the 6MWT takes longer to complete (Marinho et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Some factors can affect the skeletal muscle of people with CF, such as systemic inflammation, nutritional imbalance, electrolyte disturbances, chronic hypoxia, inactivity, and corticosteroid use (Arikan et al, 2015;Troosters et al, 2009) (Enright et al, 2007). In this regard, we observed that the TGlittre time was correlated with HGS, which is in agreement with Ozipek et al (2020), who observed an association of TGlittre time with the function of several peripheral muscle groups in children with CF. In fact, HGS is a clinical marker of poor physical performance and all-cause mortality (Lima et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, several studies demonstrated postural abnormalities in patients with chronic lung diseases. Similar to these results, Ozipek et al showed that children with CF and non‐CF bronchiectasis had impaired posture 40 . Another study stated that children and young adults with CF had more frequent spinal and lower extremity deformities 41 .…”
Section: Discussionmentioning
confidence: 58%
“…Similar to these results, Ozipek et al showed that children with CF and non-CF bronchiectasis had impaired posture. 40 Another study stated that children and young adults with CF had more frequent spinal and lower extremity deformities. 41 Lopes et al showed that children with persistent asthma had higher protraction of the head and shoulder.…”
Section: Resultsmentioning
confidence: 99%